Adaptable customer engagement strategy for utilising energy flexibility - Ilieva, Iliana; Matthews, Rose; Tobin, Paul; Valor, Carmen; Moreno , Valeria Karina; Ruiz, Leonor (International Journal of Sustainable Energy Planning and Management, 2025)
This paper provides a comprehensive framework for effectively involving customers in the utilisation of flexibility resources. The work is built upon social science principles to enhance customer recruitment, onboarding, and retention. The engagement strategy embraces methodologies such as actor-network theory and a hybrid collaboration approach. These tools are considered instrumental in shaping the engagement process, which is designed to be attractive to customers through incentives, educational initiatives, continuous feedback, and regular evaluations. A timeline and a set of engagement activities guides the implementation of the strategy. The strategy is adaptable and suggests customisation of engagements to suit different customer profiles. To measure the effectiveness and overall impact of the engagement activities, the strategy includes an evaluation component with proposed metrics. By applying the methodologies, insights, and activities detailed, the use of appropriate approaches to engage customers and foster the uptake of flexible energy practices can be facilitated.